Quiet : the power of introverts in a world that can't stop talking - Cain, Susan (New York : Crown Publishers, 2012)
This book demonstrates how introverted people are misunderstood and undervalued in modern culture, charting the rise of extrovert ideology while sharing anecdotal examples of how to use introvert talents to adapt to various situations. At least one-third of the people we know are introverts. They are the ones who prefer listening to speaking, reading to partying; who innovate and create but dislike self-promotion; who favor working on their own over brainstorming in teams. Although they are often labeled "quiet," it is to introverts that we owe many of the great contributions to society, from van Gogh's sunflowers to the invention of the personal computer. Filled with indelible stories of real people, this book shows how dramatically we undervalue introverts, and how much we lose in doing so. Taking the reader on a journey from Dale Carnegie's birthplace to Harvard Business School, from a Tony Robbins seminar to an evangelical megachurch, the author charts the rise of the Extrovert Ideal in the twentieth century and explores its far-reaching effects. She talks to Asian-American students who feel alienated from the brash, backslapping atmosphere of American schools. She questions the dominant values of American business culture, where forced collaboration can stand in the way of innovation, and where the leadership potential of introverts is often overlooked. And she draws on cutting-edge research in psychology and neuroscience to reveal the differences between extroverts and introverts. She introduces us to successful introverts, from a witty, high-octane public speaker who recharges in solitude after his talks, to a record-breaking salesman who quietly taps into the power of questions. Finally, she offers advice on everything from how to better negotiate differences in introvert-extrovert relationships to how to empower an introverted child to when it makes sense to be a "pretend extrovert." This book has the ability to permanently change how we see introverts and, equally important, how introverts see themselves.
The north and south of temperament -- The Extrovert Ideal. The rise of the "mighty likeable fellow" : how extroversion became the cultural ideal ; The myth of charismatic leadership: the culture of personality, a hundred years later ; When collaboration kills creativity: the rise of the new Groupthink and the power of working alone -- Your Biology, Your Self? Is temperament destiny? : nature, nurture, and the Orchid Hypothesis ; Beyond temperament: the role of free will (and the secret of public speaking for introverts) ; "Franklin was a politician, but Eleanor spoke out of conscience" : why cool is overrated ; Why did Wall Street crash and Warren Buffett prosper? : how introverts and extroverts think (and process dopamine) differently -- Do All Cultures Have an Extrovert Ideal? Soft power: Asian-Americans and the extrovert ideal -- How to Love, How to Work. When should you act more extroverted than you really are? ; The communication gap: how to talk to members of the opposite type ; On cobblers and generals: how to cultivate quiet kids in a world that can't hear them -- Wonderland -- A note on the words Introvert and Extrovert.
Includes bibliographical references (p. [277]-323) and index.
Keywords: Introverts; Introversion; Extraversion; Interpersonal relations; Introversion (Psychology) -- Popular Works; Extraversion (Psychology) -- Popular Works; Interpersonal relations -- Popular Works; Personality; Interpersonal relations